The Influence of Financial Factors on Profit Growth with Company Size as a Moderating Variable: Study of LQ45 Manufacturing Companies - Fairuz Amalia, Salma; Herlin Tundjung Setijaningsih (Dinasti Publisher, 2025)
The aim of this research is to determine the effect Return On Asset (ROA), Net profit Margin (NPM), Current Ratio (CR) on profit growth. And to find out whether company size as a moderating variable can strengthen ROA, NPM and CR on profit growth. This research is quantitative descriptive research using Eviews 12 software. The population in this research is manufacturing companies which are members of the LQ45 index during the research period, namely 2018-2022, totaling 18 companies. Sample selection using purposive sampling and obtained 12 companies that would become research samples. The research results show that variables Return On Asset (ROA), Net profit Margin (NPM), Current Ratio (CR) has a significant positive effect on profit growth. Meanwhile, company size chosen as a moderating variable can strengthen the positive influence of ROA, NPM and CR on profit growth.